PROSPEK PENGEMBANGAN AGRIBISNIS PORANG DI KOTA PEKANBARU - Ribka Betharia Pasaribu; Syaiful Hadi; Sakti Hutabarat (Fakultas Pertanian, Universitas Riau, 2021)
Porang agribusiness has prospects to be developed because porang is a plant that has various benefits. Porang farming in recent years has only been carried out by farmers in Pekanbaru City. Porang farming certainly has its own challenges if it is planted in Riau, especially in Pekanbaru City. Farmers hope that porang farming can provide maximum profit. This study aims to: (a) Analyze the prospects for developing porang agribusiness in Pekanbaru City and (b) Analyze porang farming in Pekanbaru City. This research was conducted from February 2021 to December 2021. Descriptive rating scale analysis and farming analysis were applied in this study to analyze the prospects for the development of porang agribusiness in Pekanbaru City. The results of this study indicate that the prospect of developing porang agribusiness in Pekanbaru City is prospective and can provide benefits. This is because porang can adapt well in Pekanbaru City if farmers cultivate porang according to the recommendations of Good Agricultural Practice for Food Crops (Ministry of Agriculture Number 48 of 2006) and Good Agricultural Practice of Porang Cultivation (Department of Agriculture Mojokerto in 2020), although the recommendations for porang cultivation are specifically for Riau doesn't exist yet.